Murals and tourism heritage, politics and identity - Skinner, Jonathan; Jolliffe, Lee (Heritage, Culture and Identity, 2016)
Around the world, tourists are drawn to visit murals painted on walls. Whether heritage asset, legacy leftover, or contested art space, the mural is more than a simple tourist attraction or accidental aspect of tourism material culture.